Actinidia chinensis Planch Root extracts trigger ferroptosis in colorectal cancer via the p53/SLC7A11/GPX4 axis - Ma, Chenyang; Chen, Ruixiu; Wang, Hangxuan; Qiu, Kaijie; Xia, Qing; Yang, Shaohui; Wang, Jianan; Cheng, Zisheng; Cui, Wei; Lu, Jun; Duan, Shiwei (Frontiers in Pharmacology, 2026)
PurposeColorectal cancer (CRC) remains a leading cause of cancer-related mortality worldwide. Actinidia chinensis Planch Root extracts (acRoots), a traditional Chinese medicine (TCM), possess recognized anticancer properties, but their efficacy and mechanism in Colorectal cancer are not fully understood. This study investigates the role of acRoots in suppressing Colorectal cancer progression, with a specific focus on its potential to induce ferroptosis, a form of iron-dependent cell death.MethodsThe anti-tumor effects of acRoots were evaluated in human Colorectal cancer cell lines (HCT-15, CW-2) using Cell Counting Kit-8 (CCK-8), colony formation, wound healing, and Transwell assays. Cell death was analyzed by Annexin V-FITC/PI flow cytometry. Mechanisms were probed by measuring reactive oxygen species (ROS), glutathione (GSH) levels, malondialdehyde (MDA) levels, and performing qRT-PCR and Western blot for ferroptosis-related markers (SLC7A11, GPX4, p53). The ferroptosis inhibitor Ferrostatin-1 (Fer-1) was used in rescue experiments. The in vivo antitumor efficacy was assessed in HCT-15 xenograft models in nude mice treated orally with acRoots (150 mg/kg/day) for 14 days.ResultsThe acRoots significantly and dose-dependently inhibits the viability, proliferation, migration, and invasion of colorectal cancer cells. Concurrently, acRoots effectively induces ferroptosis in these cells, characterized by intracellular reactive oxygen species (ROS) accumulation, glutathione (GSH) depletion, and a significant increase in the lipid peroxidation product malondialdehyde (MDA). These ferroptosis-related phenotypes can be reversed by the ferroptosis-specific inhibitor Ferrostatin-1 (Fer-1). Mechanistically, acRoots upregulates the expression of the tumor suppressor gene p53, subsequently downregulating the expression levels of key ferroptosis regulators SLC7A11 and GPX4. Furthermore, pretreatment with Fer-1 effectively reverses acRoots-induced cytotoxicity and ROS accumulation. In an HCT-15 xenograft mouse model, oral administration of acRoots (150 mg/kg/day) significantly inhibited tumor growth, reduced intratumoral GSH levels, and no obvious toxicity was observed.ConclusionOur findings demonstrate that acRoots exerts potent anti-Colorectal cancer effects by inhibiting malignant phenotypes and inducing ferroptosis. This ferroptosis is mediated, at least in part, through the p53-dependent downregulation of the SLC7A11/GPX4 axis. These results position acRoots as a promising therapeutic candidate and a novel natural ferroptosis inducer for Colorectal cancer treatment, warranting further clinical investigation.